Activity of the ethanolic extract of propolis (EEP) on quorum sensing-mediated pigment production in chromobacterium violaceum and virulence factor production in pseudomonas aeruginosa - Lamberte, Lisa E.; Rivera, Windell L. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2009)
Bacteria are capable of the organized expression of specific sets of genes through a recently-discovered phenomenon termed quorum sensing (QS). Researchers have begun to focus their efforts into the discovery of potential quorum sensing inhibitors for the development of novel antipathogenic drugs. This study investigated the quorum sensing inhibitory potential of the ethanolic extract of propolis (EEP) in the test organism Chromobacterium violaceum ATCC 12472 and the opportunistic organism Pseudomonas aeruginosa PAO1. Results of this study showed that EEP was able to inhibit the quorum sensing-mediated violace in production in C. violaceum. EEP was thereby subjected to further testing on its ability to interfere with the quorum sensing-regulated virulence factor production and biofilm formation in P. aeruginusa.
Thesis (M.S. Microbiology)--University of the Philippines Diliman
Keywords: Quorum sensing (Microbiology) -- Inhibitors -- Philippines; Pseudomonas aeruginosa -- infections -- Philippines